The enzymatic markers of the adaptation of Cinara tujafilina to changing the host plant. Issue 5 (3rd September 2018) - Durak, Roma; Molon, Mateusz; Durak, Tomasz; Chrzanowski, Grzegorz
Abstract : Interactions occurring between the insect and its host plant are an important aspect of understanding the process of species dispersal and the colonisation of new host plants. Aphid adaptive processes in response to the changing vegetation cover include morphological, developmental, behavioural, and metabolic adaptations. The activity of enzymes is presumed to be involved in protecting the insects from the toxic effects of oxidative stress and is an enzymatic defense mechanism for insects. The activity of antioxidant (superoxide dismutase and catalase), detoxifying (glutathione S-transferase and β-glucosidase), and oxidoreductive (peroxidase and polyphenol oxidase) enzymes in the tissues of Cinara (Cupressobium) tujafilina (Del Guercio) aphids during host switch were studied. The performed studies have demonstrated that the environmental stress represented by the host switch induces the aphid organisms to produce an instant response manifested as increased SOD and CAT activity in only 24 hr after the colonisation of a new host plant. Host plant changeover caused a significant increase in the average β-glucosidase activity in C. tujafilina tissues as early as after 24 hr. Also, the increased GST activity level persisted in aphid tissues throughout the entire experiment, which was 96 hr. The results of our study have demonstrated that switching a host plant by aphids activates both oxidoreductases (PPO, POD) in the tissues of C. tujafilina . They have also confirmed that these enzymes act in a complementary fashion in the aphid body. Due to the flexible activity of enzymes, C. tujafilina is able to rapidly respond and adjust to various hosts, thus achieving adaptive success.